2008
DOI: 10.1152/ajpheart.01152.2007
|View full text |Cite
|
Sign up to set email alerts
|

Identity of the renin cell is mediated by cAMP and chromatin remodeling: an in vitro model for studying cell recruitment and plasticity

Abstract: Pentz ES, Sequeira Lopez ML, Cordaillat M, Gomez RA. Identity of the renin cell is mediated by cAMP and chromatin remodeling: an in vitro model for studying cell recruitment and plasticity. Am J Physiol Heart Circ Physiol 294: H699-H707, 2008. First published November 30, 2007 doi:10.1152/ajpheart.01152.2007.-The renin-angiotensin system (RAS) regulates blood pressure and fluid-electrolyte homeostasis. A key step in the RAS cascade is the regulation of renin synthesis and release by the kidney. We and others … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
105
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(110 citation statements)
references
References 47 publications
5
105
0
Order By: Relevance
“…We have previously shown that the cAMP/CBP/p300/CREB pathway is fundamental in the control of renin synthesis and release. 4,22 A similar analysis was also performed for the renin enhancer ( Figure 6B) that begins at Ϫ2500 for the mouse and Ϫ11,015 for the human, and, in each case, extends about 275 bases further 5Ј. The presence of an estrogen response element (V$EREF) is intriguing.…”
Section: Transcriptional Control Of the Renin Phenotypementioning
confidence: 84%
See 1 more Smart Citation
“…We have previously shown that the cAMP/CBP/p300/CREB pathway is fundamental in the control of renin synthesis and release. 4,22 A similar analysis was also performed for the renin enhancer ( Figure 6B) that begins at Ϫ2500 for the mouse and Ϫ11,015 for the human, and, in each case, extends about 275 bases further 5Ј. The presence of an estrogen response element (V$EREF) is intriguing.…”
Section: Transcriptional Control Of the Renin Phenotypementioning
confidence: 84%
“…4 We isolated YFP ϩ cells from the kidney of newborn and adult mice, and from adult mice subjected to a physiologic challenge that elicits the retransformation of arteriolar smooth muscle cells (aSMCs) to the renin phenotype, and compared their gene profiles to those from multiple cell types of the nephron at variousstagesofdevelopment(Figure1B). 5 Finally,todefinewhether the set of genes expressed by the renin cell located at the pole of the glomerulus-the bonafide adult JG cell-is different from the set of genes expressed by other renin cells, we developed a single cell isolation and amplification procedure that allowed us to uncover the expression profile of the classical JG cell.…”
mentioning
confidence: 99%
“…Recently, in vitro and in vivo studies demonstrate the crucial role of the cAMP pathway on the acquisition and maintenance of the renin cell identity. 51,52 Activation of the cAMP pathway was proven to be of importance not only for the well known stimulation of renin release but also for vascular development early in fetal life. Conditional deletion of G␣ s in cells from the renin lineage such as arteriolar SMCs and mesangial cells results in almost complete absence of renin-expressing cells in the fetal kidney accompanied by blunted development of the preglomerular arterial tree.…”
Section: Role Of the Camp Pathwaymentioning
confidence: 99%
“…Different mechanisms seem to control the phenotype of renin-expressing cells (3,14,15,17,26,29,32). Interactions of renin cells with other cell types are likely to be crucial to promote, maintain, and regulate the expression of renin.…”
mentioning
confidence: 99%